Functioning of participatory budgets: current state, modernization trends and modeling in the context of reforming public finances - Lobodina, Zoriana; Demianyshyn, Vasyl; Kizyma, Tetiana; Berezka, Kateryna; Kizyma, Andrii (Herald of Economics, 2023)
Introduction. A necessary condition for the reconstruction of Ukraine from the consequences of the destruction caused by the Russian armed aggression, the COVID-19 pandemic, and the formation of a resource-saving inclusive economy on the basis of permanent socio-economic growth is the effective functioning of the public finance management system, the basic element of which is budgeting technologies. Participatory budgeting is their important component, and participatory budget is one of the innovative tools for involving citizens in the distribution and use of budget resources, democratization of the budget process at the local level to stimulate the development of territorial communities and regions.Purpose. The purpose of the article is to develop theoretical and methodological foundations and practical approaches to the functioning of participatory budgeting, to identify the main trends in the development of participatory budgeting and to substantiate the directions of its modernization in the context of reforming public finances.Methods. To achieve the goal defined in the study, general scientific methods were used: analysis and synthesis, induction and deduction (for the formation of the theoretical foundations of participatory budgeting); functional and statistical analysis, analogy, systematization, formalization, measurement, modeling (to assessthe practice of functioning of budgets) participation); generalization, comparison, optimization, argumentation, logical methods (for developing directions for improving participatory budgeting).Conclusions. A theoretical approach to the disclosure of the essence of participatory budgeting has been formed, an algorithm for its implementation at the level of the territorial community is given and the advantages of functioning of participatory budgets are outlined. The practice of using participatory budgeting in Ukraine at different levels of the budget system is analyzed, a number of problems are identified, among which the most important is the choice of allocation directions, use of participatory budgeting resources and criteria for their optimization, and approaches to their solution are proposed. A scientific approach to optimizing the expenditures of the participatory budgeting using economic and mathematical modeling has been formed.Discussion. The prospects for further research are the need to solve the problems of effective use of budget resources of local self-government bodies in the conditions of war and to find ways to ensure compliance of priority directions of expenditures of participatory budgets with the strategic goals of socio-economic development of territorial communities and regions.